IMPLEMENTASI PERDA NOMOR 18 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PENYANDANG DISABILITAS DI PEKNABARU (STUDI KASUS PENYEDIAAN AKSESSIBILITAS BIDANG SARANA DAN PRASARANA TRANSPORTASI) - Agnesia Allensky; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Disability community is a citizen of the Republic of Indonesia in the Act of 1945 is guaranteed to have the status, rights, obligations, and the same role with other citizens. Therefore, the government should give adequate attention to the disabled, including in terms of provision of services, especially the accessibility of land transport infrastructure. Reality has shown the opposite. Social services and the mobility of persons with disabilities are lacking a proper where most of the accessibility barriers still prevalent. This makes disabled people disenfranchised in getting similar services and even to say good. based on that researcher interest to study how the Implementation Regulation No. 18 Year 2013 on the Protection and Empowerment of Persons with Disabilities In the city of Pekanbaru (Case Study accessibility Provision of Infrastructure and Transport Infrastructure. The concept of the theory used is the theory of implementation according to Van Meter Van Horn (2008), which says that there are several variables that affect the performance of a public policy implementation. This research uses qualitative method with descriptive data assessment. techniques of data collection is done by observation, interviews, and documentation which the parties involved in this study as an informant. The results of this study indicate that the process of implementation of the regulation number 18 of 2013 on the protection and empowerment of persons with disabilities can not be executed properly. The standards that have been set have not been implemented properly. Still many of its implementation is not in accordance with established standards. keywords: Disability, accessibility, mobility, Implementation